Null entity - Haddon, Seth (Haddon, Seth. Volatile Memory duology., 2026)
With her identity erased from the Corporate Federation, Wylla is a ghost in the machine: untraceable, unpredictable, and fueled by vengeance. She fights alongside Sable, the digital consciousness she loves in ways no system could ever define. Together, they've built a reputation for tearing through VisorForge's carefully constructed lies. But notoriety has a cost. When one of their attacks draws the attention of the Edenic Order-a clandestine eco-resistance whose insurgents bloom with Old Earth flora-Wylla and Sable are offered something more than revenge: a chance to dismantle VisorForge from the roots up. As they fall deeper into the Order's radical vision, tensions rise. Wylla: aching to change the world yet seduced by thoughts of a quiet life, free of bloodshed. Sable: pushed to her moral limits when what she's wanted since death is at her fingertips. To survive, they'll need to embrace what makes them dangerous: two minds, one body, and a shared resolve to bring down a corporatized dystopia-no matter the cost.